2015
DOI: 10.1002/adma.201503176
|View full text |Cite
|
Sign up to set email alerts
|

Angular Dependence of Exchange Bias and Magnetization Reversal Controlled by Electric‐Field‐Induced Competing Anisotropies

Abstract: The combination of exchange-biased systems and ferroelectric materials offers a simple and effective way to investigate the angular dependence of exchange bias using one sample with electric-field-induced competing anisotropies. A reversible electric-field-controlled magnetization reversal at zero magnetic field is also realized through optimizing the anisotropy configuration, holding promising applications for ultralow power magnetoelectric devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
83
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 36 publications
4
83
0
1
Order By: Relevance
“…9(a), leading to realization of repeatable electrical magnetization reversal at zero oersted. 56 For zero magnetic field, the angular dependences of magnetization at various electric fields with standard trigonometric function behaviors are presented in Fig. 9(b), suggesting the agreements between experiment results and simulations.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…9(a), leading to realization of repeatable electrical magnetization reversal at zero oersted. 56 For zero magnetic field, the angular dependences of magnetization at various electric fields with standard trigonometric function behaviors are presented in Fig. 9(b), suggesting the agreements between experiment results and simulations.…”
supporting
confidence: 52%
“…55 Whereas this switching of magnetization by electric field is irreversible, i.e., once the magnetization switches and it cannot switch back to the original orientation only by varying electric field. Very recently Chen et al 56 demonstrated reversible electrical magnetization reversal at room temperature in CoFeB/IrMn/PMN-PT multiferroic heterostructures, which integrates exchange-biased structures and FE materials. Figure 8(a) shows the sample structure with the pinning direction along the [100] direction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…37,38,41,116,[180][181][182][183][184][185][186][187][188][189][190][191][192] We term these four types of converse magnetoelectric coupling mechanisms as 'charge densities', 'interfacial oxidation', 'exchange coupling', and 'strain transfer', respectively. Note that the change of magnetization (ΔM) can be global (that is, average of an entire heterostructure), which can be measured directly using, for example, a superconducting quantum interference device or indirectly from the Hall transport measurement; the ΔM can also represent the magnetization change within a local surface area (precisely, including surface regions within the probe depth) of the sample, which can be measured through various magnetic domain imaging techniques (see a summary in ref.…”
Section: Dimension Of Nanomagnet Strain-controlled Magnetic Domain-wamentioning
confidence: 99%
“…In contrast to CEB, the spontaneous exchange bias(SEB) could be observed without the assistance of external magnetic field. Thus the SEB would be of easy to electric field control of EB devices as it eliminates the requirement of external magnetic field to create the unidirectional anisotropy910. SEB was first reported in NiMnIn alloys by Wang et al 11.…”
mentioning
confidence: 99%